Efficacy and Safety of Low-dose Oral Prednisolone for Patients with Refractory Hunner-type Interstitial Cystitis - Yoshiyuki Akiyama; Aya Niimi; Akira Nomiya; Satoru Taguchi; Yuta Yamada; Yusuke Sato; Daisuke Yamada; Daichi Maeda; Tetsuo Ushiku; Haruki Kume; Yukio Homma (European Urology Open Science, 2023)
Background: Hunner-type interstitial cystitis (HIC) is an immunological, chronic inflammatory disease. The efficacy of corticosteroid as a treatment for HIC is unclear. Objective: To assess the efficacy and safety of low-dose oral prednisolone (PSL) treatment for patients with refractory HIC. Design, setting, and participants: This retrospective observational study reviewed the clinical outcomes of 31 patients with refractory HIC who received oral PSL daily (initial dose, 5.0 or 7.5 mg) for at least 12 mo between 2016 and 2023. The dose was tapered to the minimum that maintained symptom relief during follow-up. Outcome measurements and statistical analysis: Treatment outcomes were evaluated using a seven-graded global response assessment (scores ≥+2, moderately or markedly improved, were defined as treatment response), O’Leary and Sant symptom and problem indices (OSSI/OSPI), overactive bladder symptom score (OABSS), an 11-point pain intensity numerical rating scale, a quality of life (QOL) score, and frequency-volume chart variables. Related complications were also documented. Results and limitations: The mean follow-up period was 20.1 ± 14.6 mo. The overall response rates at 1, 3, 6, 9, and 12 mo at doses of 6.7, 6.7, 5.2, 4.0, and 3.0 mg were 38.7%, 48.4%, 54.8%, 61.3%, and 64.5%, respectively. Compared with baseline, OSSI/OSPI and pain intensity improved significantly from 1 mo after PSL induction. The OABSS, QOL score, urinary frequency, and voided volume improved significantly from 9 mo after PSL induction. No patients discontinued treatment due to adverse events, although hypertension and glucose intolerance occurred in two patients, but these were resolved by temporal medications. Conclusions: This study showed that low-dose oral PSL significantly improves bladder pain, urinary symptoms, and QOL in patients with HIC, without serious adverse events. Further prospective evaluation is warranted to verify the potential efficacy and safety of low-dose PSL for HIC. Patient summary: This retrospective observational study reviewed the clinical outcomes of 31 patients suffering from refractory Hunner-type interstitial cystitis treated with low-dose oral prednisolone. Low-dose prednisolone improved bladder pain, urinary symptoms, and quality of life significantly, without serious adverse events. The response rate of 64.5% at 12 mo was comparable with the rates reported in previous studies that used higher doses of prednisolone. This study provides a rationale for further prospective evaluation of low-dose prednisolone for this intractable disease.